Cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation

Through the strategy of inducing multi-nuclear encapsulation in a cyclodextrin metal organic framework, cyclodextrin polymer microcapsules that can gel controlled release silver nanoparticles were prepared, solving the problems of poor stability and uncontrollable release in applications, and achieving efficient and uniform silver nanoparticles distribution and dual-stage release characteristics.

CN119744857AActive Publication Date: 2025-04-04ANHUI UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510262026.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-06
Publication Date
2025-04-04
Estimated Expiration
2045-03-06

AI Technical Summary

Technical Problem

In the prior art, silver nanoparticles have problems in application, such as a tendency to agglomerate, poor stability and uncontrollable release, resulting in poor application effect in the field of antibacterials and may be toxic to host cells.

Method used

Through the strategy of inducing multi-nuclear encapsulation in a coordinated nucleation growth, porous crystals of cyclodextrin metal organic frames with uniform dispersed silver nanoparticles within are synthesized in one step, and then cyclodextrin polymer microcapsules that can be gelatinized controlled release silver nanoparticles are obtained.

Benefits of technology

The efficient boundary and uniform distribution of silver nanoparticles in the cyclodextrin skeleton pores of porous crystals is achieved, avoiding the problem of silver nanoparticles loading on the surface of microcapsules. The size of silver nanoparticles is small and uniformly distributed, achieving the dual-stage release characteristic of "fast onset-long-term maintenance".

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119744857A_ABST
    Figure CN119744857A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of polysaccharide antibacterial agents, and discloses a cyclodextrin polymer microcapsule capable of realizing controlled release of silver nanoparticles through gelatinization, and a preparation method of the cyclodextrin polymer microcapsule comprises the following steps: firstly, synthesizing a porous crystal of a cyclodextrin metal organic framework in which the silver nanoparticles are uniformly dispersed in one step through a strategy of synergistic nucleation growth induction multi-core packaging; and then cross-linking to obtain the cyclodextrin polymer microcapsule capable of controlling the release of the silver nanoparticles through gelatinization. According to the synthesis strategy, all the silver nanoparticles are limited in cyclodextrin skeleton pore channels of the porous crystal, the problem that the silver nanoparticles are loaded on the surface of the cyclodextrin polymer microcapsule is avoided, and the silver nanoparticles are small in size and uniform in distribution; the prepared microcapsule is gelatinized when encountering water, controllable release of the silver nanoparticles can be achieved, and the microcapsule has good application potential in the fields of antibiosis, catalysis, pollutant detection and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of polysaccharide antibacterial agents, and in particular relates to a cyclodextrin polymer microcapsule capable of controlled release of silver nanoparticles through gelation. Background Art

[0002] Silver nanoparticles (AgNPs) have shown broad application prospects in biomedicine, catalysis and sensing due to their unique optical, electrical and antibacterial properties. However, the problems of aggregation tendency, poor stability and uncontrollable release in practical applications have seriously restricted their large-scale application. In terms of antibacterial, the use of silver nanoparticles alone also has problems such as reduced antibacterial effect due to easy aggregation, or easy to be quickly cleared and unable to play a long-term role, and possible toxicity to host cells. To solve these challenges, the construction of efficient loading strategies has become the current research focus. Polymer microcapsules, as a functional material with high biocompatibility, shell structure, high specific surface area and adjustable physicochemical properties, provide an ideal carrier for the efficient loading of AgNPs. In antibacterial applications, compared with the direct use of silver nanoparticles (AgNPs), polymer microcapsules loaded with AgNPs can accurately control the release rate of AgNPs or silver ions through their carrier characteristics, avoiding excessive local concentration caused by one-time release, while maintaining long-term effective antibacterial concentration. In addition, the shell structure of polymer microcapsules can reduce the direct contact between AgNPs and host cells, significantly reduce cytotoxicity, and prevent AgNPs from aggregation, oxidation, or inactivation in body fluids or complex environments.

[0003] Polymer microcapsules can be prepared by first synthesizing a metal organic framework (MOF), and then preparing polymer microcapsules through a chemical cross-linking strategy. Based on this, polymer microcapsules embedded with AgNPs can be achieved through the path of "first constructing a composite MOF, then cross-linking and converting". This template method not only simplifies the preparation process of traditional microcapsules, but also can use the confinement effect of MOF to accurately control the loading sites and dispersion state of AgNPs, thereby significantly improving the controllability and repeatability of material preparation. In this process, AgNPs are precisely confined inside the MOF pores rather than on the surface, which becomes a key factor in determining the performance of the material. At present, the strategies for MOF loading AgNPs mainly include two categories: one is to first synthesize the MOF skeleton, and then grow silver nanoparticles using the MOF skeleton as a carrier; the other is to first synthesize silver nanoparticles, and then encapsulate the pre-synthesized silver nanoparticles in a metal organic framework. For example, the Shailendra Shakya group ( Small 2019, 15, 1901065.) and Chen Lei's research group at the First Affiliated Hospital of Sun Yat-sen University (CN112778772A) synthesized a cyclodextrin metal organic framework embedded with silver nanoparticles by first synthesizing a MOF skeleton and then growing silver nanoparticles on the MOF skeleton as a carrier. Although this strategy is expected to prevent the aggregation of silver nanoparticles and limit their growth, it is sometimes inevitable that some silver nanoparticles will form on the surface of the cyclodextrin metal organic framework. Therefore, this strategy still faces the challenge of non-specific deposition of AgNPs on the MOF surface. The second strategy of MOF loading AgNPs has the problem of complex preparation process and the structure of MOF is easily damaged during the process of encapsulating silver nanoparticles.

[0004] Therefore, developing simple loading strategies to achieve efficient confinement and uniform distribution of AgNPs inside MOF pores is of great significance to improving the performance and application potential of polymer microcapsule composites. Summary of the invention

[0005] Based on the problems existing in the above-mentioned prior art, the present invention develops a method for preparing cyclodextrin polymer microcapsules that can control the release of silver nanoparticles by gelation, aiming to achieve efficient confinement and uniform distribution of AgNPs inside the pores of the cyclodextrin skeleton of porous crystals based on a new loading strategy, and expand the application field of silver nanocomposite materials.

[0006] In order to achieve the purpose, the present invention adopts the following technical scheme: The method for preparing cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation is characterized in that: firstly, a synergistic nucleation growth-induced multi-core encapsulation strategy is used to synthesize porous crystals of cyclodextrin metal organic frameworks with silver nanoparticles uniformly dispersed inside in one step, and then cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation are obtained by cross-linking. Specifically, the method comprises the following steps: Step 1: Synthesize porous crystals of cyclodextrin metal organic frameworks with silver nanoparticles uniformly dispersed inside in one step through the strategy of synergistic nucleation growth induced multi-core encapsulation. The specific steps are as follows: Cyclodextrin and potassium salt were mixed and stirred with water until fully dissolved, and then methanol was added. The mixture was placed in an oil bath at 40-55°C and heated for 5-30 minutes. Then the heating was stopped and the methanol solution of the silver precursor was quickly added. The mixture was reacted for 5-10 minutes to obtain porous crystals of cyclodextrin metal organic framework with silver nanoparticles uniformly dispersed inside, which were recorded as CD-MOF@Ag NP.

[0007] Step 2: Preparation of cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation The CD-MOF@Ag NP prepared in step 1 is added to an organic solvent, and a cross-linking agent is added to carry out a cross-linking reaction. The product is collected by centrifugation, and the product is separated, purified, and vacuum-dried to obtain cyclodextrin polymer microcapsules that can control the release of silver nanoparticles by gelation, which are recorded as CL-CD-MOF@Ag NP microcapsules.

[0008] Furthermore, in step 1, the potassium salt is at least one of anhydrous potassium phosphate, potassium monohydrogen phosphate, potassium dihydrogen phosphate, anhydrous potassium bicarbonate and anhydrous potassium carbonate, the cyclodextrin is at least one of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin, and the silver precursor is one of silver nitrate, silver acetate and silver sulfate.

[0009] Further: In step 1, the potassium salt and cyclodextrin are added in a molar ratio of 1-50:1, the dosage ratio of potassium salt, water, methanol and methanol solution of silver precursor is 1.6 mmol: 5-10 mL: 3-5 mL: 1-2.5 mL, and the concentration of methanol solution of silver precursor is 1-50 mM.

[0010] Furthermore, in step 2, the organic solvent is one of methanol, ethanol, acetone, acetonitrile, isopropanol, chloroform and carbon tetrachloride.

[0011] Furthermore, in step 2, the cross-linking agent is an epoxy cross-linking agent (such as ethylene glycol diglycidyl ether), an isocyanate cross-linking agent (such as isocyanate) or an acyl chloride cross-linking agent (such as 1,7-heptanedioyl chloride).

[0012] Furthermore, in step 2, the CD-MOF@Ag NP and the cross-linking agent are added in a mass ratio of 1:1~60, and the amount ratio of the CD-MOF@Ag NP to the organic solvent is 100~200 mg: 5~10 mL.

[0013] Furthermore, in step 2, the reaction temperature of the cross-linking reaction is 30-100° C., and the reaction time is 0.5-7 days.

[0014] The CL-CD-MOF@Ag NP microcapsules prepared according to the above method are cross-linked cyclodextrin metal organic frameworks in which silver nanoparticles are uniformly embedded to form a microcapsule structure; the CL-CD-MOF@Ag NP microcapsules gel when exposed to water, and the volume expands, thereby triggering the controlled release of silver nanoparticles. The controlled release of silver nanoparticles presents a dual-stage release characteristic, which is specifically manifested as follows: when the CL-CD-MOF@Ag NP microcapsules gel when exposed to water, the volume expands by more than 4 times, first triggering the release of silver nanoparticles with a particle size of no more than 5 nm, which can basically achieve complete release within 2 hours; at this time, most of the silver nanoparticles with a particle size greater than 5 nm are still retained in the cyclodextrin polymer microcapsules, and can maintain a stable and continuous release of about 3% / h within 2-24 hours, thereby achieving a dual-stage release characteristic of "rapid onset-long-term maintenance".

[0015] The cyclodextrin polymer microcapsules prepared by the present invention that can control the release of silver nanoparticles through gelation show many application potentials: they have good antibacterial properties against Escherichia coli and can be used to prepare antibacterial agents; they can be used as catalysts to catalyze the reduction of nitroaromatic hydrocarbons, turning harmful nitroaromatic hydrocarbons into valuables; and they can be used as SERS substrates to detect organic pollutants.

[0016] The beneficial effects of the present invention are embodied in: 1. The present invention provides a method for preparing cyclodextrin polymer microcapsules that can control the release of silver nanoparticles by gelation. The raw materials used are low-priced and abundant in reserves, and the production conditions are safe and simple, which has obvious cost advantages.

[0017] 2. The cyclodextrin polymer microcapsules prepared by the present invention that can control the release of silver nanoparticles by gelation have the advantages of high selectivity, high activity, high stability, good adsorption performance, excellent dispersibility, excellent adhesion and biocompatibility, and have good potential in the fields of antibacterial, catalytic and pollutant detection.

[0018] 3. The present invention has developed a new synthesis strategy, namely the strategy of synergistic nucleation growth induced multi-core encapsulation, to synthesize porous crystals of cyclodextrin metal organic frameworks with silver nanoparticles uniformly dispersed inside in one step, and then obtain cyclodextrin polymer microcapsules that can control the release of silver nanoparticles by gelation through cross-linking. This strategy not only confines all silver nanoparticles in the pores of the cyclodextrin framework of the porous crystal, avoiding the problem of silver nanoparticles being loaded on the surface of the cyclodextrin polymer microcapsules, but also the size of the silver nanoparticles is small and evenly distributed. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a scanning electron microscope image of CD-MOF@Ag NP prepared in Example 1 of the present invention.

[0020] Figure 2 This is a mapping picture of the Ag element in the CD-MOF@Ag NP prepared in Example 1 of the present invention.

[0021] Figure 3 This is the XRD image of CD-MOF@Ag NP prepared in Example 1 of the present invention.

[0022] Figure 4 This is the XRD image of the CL-CD-MOF@Ag NP microcapsules prepared in Example 1 of the present invention.

[0023] Figure 5 Fourier transform infrared spectra of the CL-CD-MOF@Ag NP microcapsules prepared in Example 1 of the present invention and the cyclodextrin γ-CD raw material used.

[0024] Figure 6 This is a transmission electron microscopy image of the CL-CD-MOF@Ag NP microcapsules prepared in Example 1 of the present invention.

[0025] Figure 7 This is a transmission electron microscopy image of the CL-CD-MOF@Ag NP microcapsules after gelation prepared in Example 1 of the present invention.

[0026] Figure 8 This is the release curve of silver nanoparticles in CL-CD-MOF@Ag NP microcapsules in Example 3 of the present invention.

[0027] Fig. 9 These are photos of bacterial colonies of Escherichia coli exposed to different concentrations of CL-CD-MOF@Ag NP microcapsules in Example 4 of the present invention.

[0028] Fig.10 This is a bar graph of the number of bacterial colonies when Escherichia coli is exposed to different concentrations of CL-CD-MOF@Ag NP microcapsules in Example 4 of the present invention.

[0029] Fig.11 This is the time-killing curve of CL-CD-MOF@Ag NP microcapsules against Escherichia coli in Example 4 of the present invention.

[0030] Fig.12 This is a UV-Vis spectrum of the reaction solution of 4-nitrophenol catalyzed by CL-CD-MOF@Ag NP microcapsules in Example 5 of the present invention changing with time.

[0031] Fig.13 This is the detection limit diagram of R6G using CL-CD-MOF@Ag NP microcapsules as SERS substrates in Example 6 of the present invention.

[0032] Fig.14 The SERS images of bisphenol A and bisphenol AF using CL-CD-MOF@Ag NP microcapsules as SERS substrates in Example 6 of the present invention are shown.

[0033] Fig.15 Schematic diagram of the release of silver nanoparticles from the CL-CD-MOF@Ag NP microcapsules prepared in the present invention after gelation. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0035] Example 1 This example synthesizes cyclodextrin polymer microcapsules that can control the release of silver nanoparticles by gelation according to the following steps: Step 1. Mix 0.1 mmol of γ-CD and 1.6 mmol of anhydrous potassium carbonate and add 6 mL of deionized water and stir until fully dissolved, then add 5 mL of methanol, place in a 50°C oil bath and heat for 5 minutes, then stop heating and quickly add 1 mL of 10 mM silver nitrate methanol solution, react for 10 minutes, and obtain porous crystals of cyclodextrin metal organic framework with silver nanoparticles uniformly dispersed inside, recorded as CD-MOF@Ag NP.

[0036] Step 2: Add 200 mg of the CD-MOF@Ag NP prepared in step 1 to 10 mL of ethanol, and add 5 g of ethylene glycol diglycidyl ether as a cross-linking agent. Heat the reaction in an oven at 50°C for 5 days, collect the product by centrifugation, filter the product, wash it with ethanol, and vacuum dry it at 40°C for 12 hours to obtain cyclodextrin polymer microcapsules that can control the release of silver nanoparticles by gelation, which are recorded as CL-CD-MOF@Ag NP microcapsules.

[0037] The scanning electron microscopy image of CD-MOF@Ag NP obtained in this example is as follows Figure 1 As shown, it can be seen from the figure that substantially no silver nanoparticles are loaded on the surface of the cyclodextrin framework of the porous crystal.

[0038] The mapping diagram of the Ag element in the CD-MOF@Ag NP obtained in this example is shown in Figure 2 As shown, it can be seen from the figure that the silver nanoparticles are loaded in the pores of the cyclodextrin framework of the porous crystal rather than on the surface.

[0039] The XRD pattern of CD-MOF@Ag NP obtained in this example is shown in Figure 3 As shown, by comparing the PDF card of silver nanoparticles and the signal peak of simulated CD-MOF, it can be seen that CD-MOF@Ag NP was successfully prepared, and it can also be seen that the size of the synthesized silver nanoparticles is small.

[0040] The XRD pattern of the CL-CD-MOF@Ag NP microcapsules obtained in this example is shown in Figure 4 As shown, it can be seen from the figure that the size of the synthesized silver nanoparticles is small.

[0041] The Fourier transform infrared spectra of the CL-CD-MOF@Ag NP microcapsules and the cyclodextrin γ-CD raw materials obtained in this example are shown in Figure 5 As shown in the figure, it can be seen that the COC stretching vibration of cyclodextrin monomer (1020 ~ 1150 cm -1 ) is a sharp peak, which becomes broader and blunter with the occurrence of cross-linking reaction, proving the successful preparation of cyclodextrin polymer microcapsules.

[0042] The transmission electron microscopy image of the CL-CD-MOF@Ag NP microcapsules obtained in this example is shown in Figure 6 As shown, it can be seen from the figure that there are basically no silver nanoparticles loaded on the surface of the microcapsules.

[0043] 20 mg of the CL-CD-MOF@Ag NP microcapsules obtained in this example were dispersed in 1 mL of deionized water to form gelled microcapsules, and then the morphology thereof was directly characterized by transmission electron microscopy. Figure 7 This is a transmission electron microscope image of the gelled microcapsules. Figure 6 and Figure 7 It can be seen that the CL-CD-MOF@Ag NP microcapsules obtained in this example gelled when exposed to water, which can quickly trigger the release of silver nanoparticles with a particle size less than 5 nm, while most silver nanoparticles with a particle size greater than 5 nm are retained in the microcapsules. It can also be seen that in the product synthesized based on the strategy of synergistic nucleation growth induced multi-core encapsulation in this example, the silver nanoparticles are uniform in size and small in size.

[0044] Example 2 In this example, the water absorption rate of the CL-CD-MOF@Ag NP microcapsule gelation was tested according to the following steps: 200 mg of the CL-CD-MOF@Ag NP microcapsules prepared in Example 1 were dispersed in deionized water (10 mL), allowed to stand for 1 h, and then filtered with a 0.45 μm filter paper. The solid was collected and dried with additional filter paper and weighed. The water absorption rate of the CL-CD-MOF@Ag NP microcapsules was calculated by formula (1).

[0045]

[0046] where w d (mg) and w w(mg) are the initial mass of CL-CD-MOF@Ag NP microcapsules (i.e., 200 mg) and the mass after water absorption and gelation, respectively.

[0047] It has been calculated that the water absorption rate of CL-CD-MOF@Ag NP microcapsules is 598%. Therefore, the volume of CL-CD-MOF@Ag NP microcapsules will expand by more than 4 times when they come into contact with water and undergo gelation.

[0048] Example 3 This example tests the loading amount of silver nanoparticles in CL-CD-MOF@Ag NP microcapsules and the release of silver nanoparticles according to the following steps: CL-CD-MOF@Ag NP microcapsules (100 mg) were suspended in water (5 mL) using a dialysis bag (MWCO 1000). The dialysis bag was clamped at the end side and immersed in 200 mL of water. A magnetic stirrer was used to stir at 350 rpm. An equal amount of solution (3 mL) was taken out at 15 minutes, 30 minutes, 1 hour, 2 hours, 6 hours, 9 hours, 12 hours and 1 day, and an equal volume of solvent was replaced after each withdrawal. The sample was nitrated with nitric acid, and the loading amount of silver nanoparticles and the release of silver nanoparticles were determined by ICP-MS. The loading amount of silver nanoparticles in CL-CD-MOF@Ag NP microcapsules (i.e., the ratio of the mass of silver nanoparticles in the microcapsules to the total mass of the microcapsules) was tested to be about 0.6%.

[0049] The release curve of silver nanoparticles from CL-CD-MOF@Ag NP microcapsules is shown in Figure 8 As shown in the figure, it can be seen that the release of silver nanoparticles gradually increases with time. At 2h, the release amount basically reached 20%, proving that the silver nanoparticles with a particle size of no more than 5 nm in the obtained microcapsules accounted for about 20% of the total load. After 2h, silver nanoparticles with a particle size greater than 5 nm began to be released stably, maintaining a release rate of about 3% / h within 2-24h.

[0050] Example 4 This example verifies the antibacterial properties of the CL-CD-MOF@Ag NP microcapsules obtained in Example 1, and the specific steps are as follows: The CL-CD-MOF@Ag NP microcapsules prepared in Example 1 were uniformly dispersed in deionized water at a concentration of 1 mg / mL to obtain microgels.

[0051] Add 100 μL of LB broth medium to a 96-well plate, then add 100 μL of the prepared microgel to the first row of the 96-well plate, and dilute the microcapsules to a concentration of 16 μg / mL or 32 μg / mL in the well plate. Finally, add 10 μL of Escherichia coli suspension (1×10 6 CFU mL -1 ), sealed with a sealing film, and incubated at 37°C for 16 h. The sample wells without microgels were used as negative controls. After the incubation, the liquid in each well was diluted with LB broth medium by the same multiple, and then 100 μL of the diluted mixture was aspirated again with a pipette, dropped onto the surface of the culture medium, and quickly spread it evenly onto the surface of the culture medium with a coating rod, placed in a 37°C constant temperature incubator for 12 h, and observed. The antibacterial performance of the microcapsules against Escherichia coli was evaluated using the colony counting method.

[0052] In this example, the bacterial colonies of Escherichia coli exposed to different concentrations of CL-CD-MOF@Ag NP microcapsules are shown in Figure 2. Fig. 9 The bar graph of bacterial colony counts is shown in Fig.10 As shown. Fig. 9 and Fig.10 It can be seen that the CL-CD-MOF@Ag NP microcapsules synthesized in Example 1 have a good antibacterial effect on Escherichia coli, and the antibacterial effect is better with the increase of concentration.

[0053] In this example, the time-killing curve of CL-CD-MOF@Ag NP microcapsules against Escherichia coli is shown in Fig.11 As shown. Fig.11 It can be seen that the CL-CD-MOF@Ag NP microcapsules have a significant bactericidal effect on Escherichia coli in the first 2 hours. As time goes by, the bactericidal effect is not so significant but the antibacterial effect still exists. This also proves that the CL-CD-MOF@Ag NP microcapsules prepared in the present invention have a dual-stage release characteristic of "rapid onset-long-term maintenance".

[0054] Example 5 This example verifies the catalytic performance of CL-CD-MOF@Ag NP microcapsules in the catalysis of 4-nitrophenol. The specific steps are as follows: 1.5 mL of ultrapure water was placed in a 10 mL glass vial, and 50 μL of 5 mM 4-nitrophenol aqueous solution and 0.5 mL of 0.1 M sodium borohydride aqueous solution were added. The solution was yellow. 10 mg of CL-CD-MOF@Ag NP microcapsules prepared in Example 1 were added to the glass vial, and the color of the solution gradually became lighter until it became colorless and transparent. The change in absorbance was tested using a UV spectrophotometer.

[0055] The UV-Vis spectra of the reaction solution of 4-nitrophenol catalyzed by CL-CD-MOF@Ag NP microcapsules in this example are shown in Figure 2. Fig.12 As shown in the figure, it can be seen that the microcapsules have a good catalytic effect on 4-nitrophenol. At 20 minutes, 4-nitrophenol has been completely converted into 4-aminophenol.

[0056] Example 6 This example verifies the performance of CL-CD-MOF@Ag NP microcapsules as SERS substrates for detecting organic pollutants. The specific steps are as follows: The CL-CD-MOF@Ag NP microcapsules prepared in Example 1 were selected as SERS substrate materials, and different concentrations (1.0×10 -6 M, 1.0×10 -7 M, 1.0×10 -8 M, 1.0×10 -9 M, 1.0×10 -10 M, 1.0×10 -11 M, 1.0×10 -12 M) R6G solution, in order to determine the detection limit of R6G when using microcapsules as SERS substrates. The results are shown in Fig.13 As shown in the figure, it can be seen that the detection limit of CL-CD-MOF@Ag NP microcapsules as SERS substrate materials for R6G is 1.0×10 -9 M, for 1.0×10 -10 M, 1.0×10 -11 M, 1.0×10 -12 R6G of M could not be detected.

[0057] 5 mg of CL-CD-MOF@Ag NP microcapsules prepared in Example 1 were added as SERS substrates to 5 mL of 1.0×10 -6 M of bisphenol A (BPA) and bisphenol AF (BPAF) aqueous solution, stirred for 1h. Take 10μL of the solution to be tested and drop it on the slide, dry it, and use it for Raman testing. The results are as follows Fig.14 As shown in the figure, it can be seen that the CL-CD-MOF@Ag NP microcapsules can be used in the presence of bisphenol A (BPA) and bisphenol AF (BPAF) at concentrations as low as 1.0×10 -6 The Raman signal can still be detected at M. This indicates that CL-CD-MOF@Ag NP microcapsules as SERS substrates have good sensitivity to organic pollutants bisphenol A (BPA) and bisphenol AF (BPAF).

[0058] In summary, the present invention first synthesizes a porous crystal of a cyclodextrin metal organic framework with silver nanoparticles uniformly dispersed inside, and then obtains a cyclodextrin polymer microcapsule that can control the release of silver nanoparticles by gelation through crosslinking. This strategy not only confines all silver nanoparticles within the pores of the cyclodextrin framework of the porous crystal, avoiding the problem of silver nanoparticles being loaded on the surface of the cyclodextrin polymer microcapsule, but also the size of the silver nanoparticles is small and evenly distributed. Fig.15 As shown, the microcapsules prepared by the present invention undergo gelation and volume expansion when in contact with water, thereby achieving controllable release of silver nanoparticles.

[0059] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation, characterized in that: First, through the strategy of synergistic nucleation growth induced multi-core encapsulation, porous crystals of cyclodextrin metal-organic framework with silver nanoparticles uniformly dispersed inside were synthesized in one step, and then cyclodextrin polymer microcapsules that could control the release of silver nanoparticles by gelation were obtained through cross-linking.

2. The method for preparing cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation according to claim 1, characterized in that: The steps include: Step 1: Synthesize porous crystals of cyclodextrin metal organic frameworks with silver nanoparticles uniformly dispersed inside in one step through the strategy of synergistic nucleation growth induced multi-core encapsulation. The specific steps are as follows: Cyclodextrin and potassium salt were mixed and stirred with water until fully dissolved, and then methanol was added, and the mixture was placed in a 40-55°C oil bath and heated for 5-30 minutes, and then the heating was stopped and the methanol solution of the silver precursor was quickly added, and the mixture was reacted for 5-10 minutes to obtain porous crystals of cyclodextrin metal organic framework with silver nanoparticles uniformly dispersed inside, which were recorded as CD-MOF@Ag NP. Step 2: Preparation of cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation The CD-MOF@Ag NP prepared in step 1 is added to an organic solvent, and a cross-linking agent is added to carry out a cross-linking reaction. The product is collected by centrifugation, and the product is separated, purified, and vacuum-dried to obtain cyclodextrin polymer microcapsules that can control the release of silver nanoparticles by gelation, which are recorded as CL-CD-MOF@Ag NP microcapsules.

3. The method for preparing cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation according to claim 2, characterized in that: In step 1, the potassium salt is at least one of anhydrous potassium phosphate, potassium monohydrogen phosphate, potassium dihydrogen phosphate, anhydrous potassium bicarbonate and anhydrous potassium carbonate, the cyclodextrin is at least one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, and the silver precursor is one of silver nitrate, silver acetate and silver sulfate.

4. The method for preparing cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation according to claim 2, characterized in that: In step 1, the potassium salt and cyclodextrin are added in a molar ratio of 1-50:1, the dosage ratio of potassium salt, water, methanol and methanol solution of silver precursor is 1.6 mmol: 5-10 mL: 3-5 mL: 1-2.5 mL, and the concentration of methanol solution of silver precursor is 1-50 mM.

5. The method for preparing cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation according to claim 2, characterized in that: In step 2, the organic solvent is one of methanol, ethanol, acetone, acetonitrile, isopropanol, chloroform and carbon tetrachloride, and the cross-linking agent is an epoxy cross-linking agent, an isocyanate cross-linking agent or an acyl chloride cross-linking agent.

6. The method for preparing cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation according to claim 2, characterized in that: In step 2, the CD-MOF@Ag NP and the cross-linking agent are added in a mass ratio of 1:1~60, and the amount ratio of CD-MOF@Ag NP to the organic solvent is 100~200 mg: 5~10 mL.

7. The method for preparing cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation according to claim 2, characterized in that: In step 2, the reaction temperature of the cross-linking reaction is 30-100° C., and the reaction time is 0.5-7 days.

8. A cyclodextrin polymer microcapsule capable of controlled release of silver nanoparticles by gelation, obtained by the preparation method according to any one of claims 1 to 7.

9. The cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation according to claim 8, characterized in that: The cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation are cross-linked cyclodextrin metal organic frameworks in which silver nanoparticles are uniformly embedded to form a microcapsule structure; the cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation undergo gelation and volume expansion when encountering water, thereby triggering the controlled release of the silver nanoparticles.

10. Use of the cyclodextrin polymer microcapsules capable of controlled release of silver nanoparticles by gelation as claimed in claim 8, characterized in that: Used to prepare antibacterial agents; or, used as a catalyst to catalyze the reduction of nitroaromatic hydrocarbons; or, used as a SERS substrate to detect organic pollutants.

Citation Information

Patent Citations

  • Antibacterial composite hydrogel as well as preparation method and application thereof

    CN112778772A

  • Method for preparing nano-silver antibacterial agent by utilizing microcapsule embedding technology

    CN102630705A

  • Preparation method of silver-metal organic framework composite antibacterial material

    CN111109293A

  • Gamma-cyclodextrin two-dimensional porous organic polymer as well as preparation method and application thereof

    CN116284507A

  • Long-acting nano-silver antibacterial agent and preparation method thereof

    CN119032964A